Unveiling the intricate mechanisms of plant defense - Guerreiro, Julie; Marhavý, Peter (Frontiers in Plant Physiology, 2023)
Plants may lack mobility, but they are not defenseless against the constant threats posed by pathogens and pests. Pattern Recognition Receptors (PRRs), which are located on the plasma membrane, enable plants to effectively recognize intruders. These receptors function by sensing elicitors or fragments of the cell wall that arise from damage. Recent studies underscore the significance of maintaining cell wall integrity in the coordination of defense mechanisms following the detection of parasitism. Pathogen invasion often triggers alterations in cell wall structure, which leads to the release of molecules like β-glucans and oligogalacturonides. These small molecules are then recognized by PRRs, which stimulate downstream signaling pathways that involve both receptor-like kinases and calcium-dependent signaling. Here, we present the latest insights into plant signaling that play a vital role in immunity: the maintenance of cell wall integrity; the intricate interplay between receptor-like kinases; and the involvement of calcium ions. The goal of the review is to provide readers with a deeper understanding of the intricate mechanisms underlying plant defense strategies.